Integrated Growth Potential of Scenedesmus sp. using Public Market Wastewater via Phycoremediation Process - Apandi, Najeeha (International Journal of Integrated Engineering, 2020)
Malaysia has been experiencing water pollution crisis over a decade and one of the causes is the direct discharge of public market wastewater (PMWW) into the drains. Therefore, phycoremediation of wastewater especially from public market sources with microalgae is proposed. The current work aimed to investigate the potentially of Scenedesmus sp. to remove nutrient from PMWW. Nutrient profile and the ability of Scenedesmus sp. to phycoremediate was tested for five (5) different concentrations of PMWW (10, 25, 50, 75, and 100%) during 19 days of treatment process. The process involves growing the Scenedesmus sp. in the PMWW which is contributing to utilize the nutrients to grow. The results indicated that Scenedesmus sp. is effective to reduce total nitrogen (TN) (91.51%), total phosphorus (TP) (92.67%), and total organic carbon (TOC) (90.20%) for 50% concentration of PMWW. Meanwhile, for the 100% of PMWW concentration Scenedesmus sp. capable to remove TN (57.49%), TP (62.92%) and TOC (50.10%). At 50% PMWW, the maximum removal of heavy metals was also recorded which were 87.21 for Fe, 86.07% for Zn, 91.47 for Cr, and 88.97% for Cd. It concluded that Scenedesmus sp. can grow effectively in the 50% PMWW than in the 100%PMWW but still be able to reduce the rate of nutrient for all samples. These findings revealed the applicability of PMWW as a medium and economical way for microalgae biomass production.